Dyskeratosis congenita: a case report and review of literature - Shamsudin, Norashikin; Kader Ibrahim, Sabeera Begum (Persatuan Dermatologi Malaysia, 2014)
Dyskeratosis congenita (DC) is classically characterised by a mucocutaneous triad of reticulated poikiloderma, nail dystrophy and mucosal leukoplakia together with bone marrow failure and increased risk of malignancy1- 4. Due to its rarity and clinical heterogeneity it is not easily recognised and patients are often treated for other entities. We report a case of dyskeratosis congenita who presented to us with the classical triad in his late twenties after years of being treated as lichen planus.